A Multivariate Analysis of the Psychosocial Impact of Malocclusion and Self-Esteem in Adolescents - Arnoldo Brasil Muniz Júnior; Diego Patrik Alves Carneiro; Carolina Carmo de Menezes; Viviane Veroni Degan; Silvia Amélia Scudeler Vedovello; Mario Vedovello Filho (Association of Support to Oral Health Research (APESB), 2023)
Objective: To evaluate the psychosocial impact of malocclusion and self-esteem in adolescents in the Amazon region. Material and Methods: A cross-sectional study was carried out with 212 adolescents with 12-year-old enrolled in all public schools in the Boca do Acre (Amazonas, Brazil). Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ) assessed the psychosocial impact of malocclusion. The self-perception of the need for orthodontic treatment was evaluated by the Aesthetic Component (AC) of the Index of Orthodontic Treatment Need (IOTN) and Global Negative Self-evaluation (GSE), the adolescent's self-esteem. The malocclusion was clinically evaluated by the Dental Aesthetic Index (DAI). The variables with p<0.20 in the individual analyses were tested in multiple logistic regression models, and those with p<0.10 remained in the model. The adjusted odds ratio (OR) was estimated with a 95% confidence interval (CI). Results: Adolescents with low self-esteem were 2.20 (95% CI: 1.23-3.93) times more likely to have a more significant impact on dental aesthetics (p<0.05). When verified by domains, the adolescents with low self-esteem had 2.33 (95% CI: 1.31-4.17) and 1.93 (95% CI: 1.09-3.42) times more likely to impact the psychological and social domains of the PIDAQ, respectively. Conclusion: Self-esteem influenced adolescents' perception of dental aesthetics in the domains related to psychological and social impact.